KATEGORISASI DAN KARAKTERISTIK MITOS MASYARAKAT BUGIS DAN MAKASSAR - Nensilianti Nensilianti (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Categorization and Characteristics of the Myth of Bugis and Makassar Society. This study aims to inventory and reconstruct categories and characteristics (linguistic features) of myths of Bugis and Makassar through qualitative research. The myths in the oral forms were gathered from informants through in-depth interviews accompanied by recording and field notes. Data were analyzed using domain analysis, taxonomic, component, and cultural theme based on Bascom's theory (1965a). The results indicate that the Bugis myths have three categories: cosmogonic, origin, and faunal, while four categories of the Makassar myths: cosmogonic, origin, faunal, and dynasty. The characteristics of Bugis and Makassar myths tend to exhibit great similarities, either due to the influence of monogenesis or polygenesis. The fundamental difference between the Bugis and Makassar myths lies in the cosmogonic about rice, faunal about crocodiles, and human endogenic about Tu Manurung. This difference is based on the views of the Bugis and Makassar people on the origin of rice, gender, marriage, geography, and kingdom or partners area.